56 Effects of mycotoxins and selected feed additives on viability and tight junction integrity of IPEC-J2 cells - Lu, Hang (J Anim Sci, 2020)
Mycotoxins are deleterious feed contaminants routinely found in cereal gains used in livestock feed. Development of strategies to eliminate mycotoxins and mitigate their harmful effects on the animal is of major importance to the livestock industry. The objective of the current study was to determine the effects of deoxynivalenol (DON), aflatoxin B1 (AFB1) and fumonisin B1(FB1), and selected prebiotic, probiotic, and essential oil blended feed additives, on viability and integrity in porcine intestinal epithelial cell line (IPEC-J2). IPEC-J2 cells were treated with each individual mycotoxin (DON, AFB1 and FB1) with or without additives (Microsecure (MS), Biolex (BL) and Encinnate (EN), Biomatrix Inc., U.S.A). Mycotoxins significantly decreased the trans-epithelial electrical resistance (TEER) of IPEC-J2 cells compared to control with no negative effects on cell viability at 72h. Biolex and EN increased TEER under a DON challenge. The decrease in TEER by AFB1 was minimized in the presence of MS (9.8%), BL (17.1%) and EN (22.8%) relative to AFB1 (P < 0.0001). The protein abundance of claudin 3 was decreased with mycotoxins (P < 0.0001) and this was partially reversed by the additives relative to control cells with additives. In addition, BL and EN significantly increased claudin 4 protein abundance (P = 0.02) when challenged with AFB1. Encinnate significantly increased TLR2 gene expression when challenged with DON (P < 0.05) with MS and BL had a numerical TLR2 gene expression. A numerical increasing of TLR2 gene expression was also observed with feed additives when cells were challenged with AFB1 and FB1. In summary, mycotoxins led to impaired epithelial tight junction integrity and this was in-part rescued by the additives tested through restoration of cellular integrity and TLR-2 dependent immune modulation.